AIM lean (adaptive–innovative–management lean) as a driver of innovative development of enterprises in Uzbekistan - Alikulov Mirzhakhon (THE INNOVATION ECONOMY, 2026)
In the context of digital transformation and the development of the intellectual economy, enterprises in Uzbekistan face the challenge of adopting new management models that can ensure innovative growth and sustainable competitiveness. One of the key directions is the adaptation of the Lean management concept, which has proven its effectiveness worldwide but requires modification to meet the specifics of transitional economies. This article substantiates the theoretical and methodological significance of the AIM Lean model, which integrates classical Lean production principles with digital technologies and intelligent strategic management tools. The author proposes a conceptual framework illustrating the interconnection between AIM Lean and innovative development, as well as provides a comparative analysis of traditional Lean management and AIM Lean. The theoretical contribution lies in the development of a new approach to enterprise management aimed at sustainable growth, digitalization, and innovation. The practical significance of the study is determined by the potential application of the AIM Lean model in industrial enterprises of Uzbekistan to increase efficiency and build long-term competitive advantages.